Interview with Professor Rich Falco, Worcester Polytechnic Institute. - Macpherson, Heather J. (Worcester Review, 2013)
An interview with music professor Rich Falco of the Worcester Polytechnic Institute is presented. When asked about how did jazz come into his life, Falco said that it was through his high school friends that he was fascinated by the type of music and that he was attracted to professional jazzers who spun magical lines of music out of their own inventiveness. He cites Herb Pomeroy as his greatest influence and mentor.